The Effect of Sorority Membership on Eating Disorders and Body Mass Index - Susan Averett; Sabrina Terrizzi; Sabrina Yang Wang Terrizzi (Institute for the Study of Labor (IZA), 2013)
Eating disorders affect 12-25% of college women. Previous research established a positive correlation between sorority membership and eating disorders. We investigate a possible causal link between sororities and weight-related behaviors and eating disorders using data from the American College Health Association. Using Propensity Score Matching and Instrumental Variable methods, we confirm that sororities exert a negative effect on the weight-related behaviors of their members. However, females who are more resilient to these outcomes self-select into sororities, implying that females in sororities are less adversely affected by them than a female who was randomly selected to join a sorority would be.
Keywords: I12; I18; 330; obesity; underweight; BMI; sorority; anorexia; bulimia; eating disorders; weight control